Analysis of Fraud in National Health Insurance in Indonesia: A Literature Review - Ice Nurlianti; Syari Winarti; Putih Sujatmiko; Erlina Puspitaloka Mahadewi (CV. Inara, 2025)
The study concern to know how Indonesia implemented the National Health Insurance Program (JKN) as a form of Universal Health Coverage (UHC) aimed at improving public welfare through access to quality and comprehensive health services. However, in its implementation, the program has faced significant challenges in the form of fraud, which has the potential to cause major financial losses and operational inefficiencies. This study used a systematic literature review methodology. This method was chosen to gain a comprehensive understanding of the patterns, causal factors, and effects of fraud reported in numerous studies and cross-national insurance schemes, both public and private. The literature review was conducted using scientific databases such as Google Scholar, PubMed, ScienceDirect, the official Indonesian website and government regulation. The analysis of the study shows that fraud can be committed by various parties involved in the JKN program, including participants, healthcare providers, BPJS Kesehatan officials, and drug/medical device providers, and collusion between these parties may even occur. Common types of fraud include manipulating medical procedures to inflate service costs (upcoding), using fictitious patient identities, forging documents, misusing cards, and billing for services not medically indicated. Challenges in addressing fraud include the scale and complexity of the program, suboptimal technology integration, changing modus operandi of perpetrators, as well as cultural and legal proof challenges.